Keragaman Isolat Khamir Osmofilik pada Madu Hutan dari Sulawesi Tengah Ditinjau Menggunakan Teknik RAPD - Ferinta Rahmayanti; Miftahul Ilmi (Fakultas Biologi | Universitas Jenderal Soedirman, 2019)
Honey is a sweet substance with high sugar content produced by bees from flower nectar. Osmophilic yeast is one of organisms that can grow in honey because their ability to adapt in high osmotic pressure environment. Twenty-seven osmophilic yeast isolates were obtained from 11 forest honey samples to this research. This research objective is to determine the diversity of yeast isolates from genotypic characterization. Genotypic characterization was done using DNA fingerprint analysis using the RAPD PCR technique. This research used 2 types of primers, namely CDU primer (5′-GCGATCCCCA-3 ′) and M13 primer (5′-GAGGGTGGCGGTTCT GAGGGTGGCGGTTCT-3 ′). Data in the form of electrophoregram are represented in table n (yeast strain) x t (character units) using binary scoring type. The data were analyzed using a numerical taxonomy method with similarity (OTU) and determined using Jaccard coefficient (SJ) in 70% of IS limit. The results of this research showed that 27 yeast isolates were divided into 2 clusters and 10 outliers with a correlation coefficient (r) of 0.924624